Knowledge, Attitudes, and Practices toward COVID-19 among Indian Residents during the Verge of Lockdown Restrictions: A Quick Online Cross-Sectional Survey - Ponnam, Hima Bindu; Akondi, Butchi Raju; Jagadabhi, Santosh Kumar; Rompicherla, Kiranmayee G.R.; Chakali, Bharathi; Mohammed, Irfan (Journal of Health and Allied Sciences NU, 2020)
Introduction Prodigious restrictions and safety measures have been adopted by the government to control the spread of wildfire coronavirus disease 2019 (COVID-19) pandemic in India. However, the effective implementation of these measures depends upon the knowledge, attitudes, and practices (KAP) of the people. In this context, a cross-sectional online survey of a sample of Indian residents for assessing their KAP toward COVID-19 has been taken up during the verge of lockdown restrictions.Methods A self-developed online KAP questionnaire consisted of 21 questions related to clinical treatment and prevention aspects of COVID-19 including the safety measures completed by the participants. Assessments on their attitudes and practices toward COVID-19 included the confidence of people to overcome this pandemic and adapting safety measures such as wearing mask while going out in recent days.Results and Discussion A sample of 1,043 participants participated in this online survey. The overall correct rate of the knowledge questionnaire was 90%. More than half of the respondents (53.3%) had confidence that India can win the battle against COVID-19. All the participants believed that Ayurveda, Yoga, Unani, Siddha, and Homoeopathy (AYUSH) systems of medicine that are the rich heritage of India would be helpful in combating the viral illness (95.4%). Nearly all the participants (99%) wore masks when going out in recent days. In multiple logistic regression analyses, the COVID-19 knowledge score was significantly associated with a lower likelihood of negative attitudes and preventive practices toward COVID-19.Conclusion The Indian residents showed good knowledge toward COVID-19 and this in turn helped them to hold optimistic attitudes and have appropriate practices toward COVID-19. More community-based health education program strategies if aimed would help further. The limitation of sample representativeness restricts to generalize the findings to population of rural areas with low socioeconomic status.
Keywords: COVID-19; knowledge; attitude; practice; cross-sectional survey; online survey; India; lockdown; AYUSH